2009
DOI: 10.1088/1126-6708/2009/08/015
|View full text |Cite
|
Sign up to set email alerts
|

A trouble with Hořava-Lifshitz gravity

Abstract: We study the structure of the phase space in Hořava-Lifshitz theory. With the constraints derived from the action, the phase space is described by five fields, thus there is a lack of canonical structure. The Poisson brackets of the Hamiltonian density do not form a closed structure, resulting in many new constraints. Taking these new constraints into account, it appears that there is no degree of freedom left, or the phase space is reduced to one with an odd number of fields.1 Some papers also pointed out the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
189
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(197 citation statements)
references
References 15 publications
8
189
0
Order By: Relevance
“…Indeed, whenever Þ 0 the lapse N is no longer a Lagrange multiplier, and the Hamiltonian constraint (obtained as the variation of the action with respect to N, H S N ¼ 0) together with the equation N ¼ 0 form a pair of second-class constraints (they have a nonvanishing Poisson bracket), which can be used to eliminate N and N . Hence, the pathologies [6,15] present in Hořava's original proposal do not appear.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, whenever Þ 0 the lapse N is no longer a Lagrange multiplier, and the Hamiltonian constraint (obtained as the variation of the action with respect to N, H S N ¼ 0) together with the equation N ¼ 0 form a pair of second-class constraints (they have a nonvanishing Poisson bracket), which can be used to eliminate N and N . Hence, the pathologies [6,15] present in Hořava's original proposal do not appear.…”
mentioning
confidence: 93%
“…The pathologies include strong coupling at energies above a very low-energy scale and fast instabilities, and appear both in the nonprojectable [5][6][7] and projectable [7][8][9] cases. These problems can be traced back to the anomalous structure of the quadratic action for the new scalar mode around smooth backgrounds, such as Minkowski space-time.…”
mentioning
confidence: 99%
“…It can be shown that only the sixth-order derivative terms in the potential are more than 60 [27]. It should be also noted that giving up the projectability condition often causes the theory to suffer the inconsistence problem [36]. However, Kluson recently showed that the Hamiltonian formalism of the BPS model is very rich, and that the algebra of constraints is well-defined [37].…”
mentioning
confidence: 99%
“…Thus, this theory leads to a modification of the Einstein's general relativity at high energies producing interesting features in cosmology. Furthermore Horava-Lifshitz gravity has been studied and extended in detail [29][30][31][32][33][34][35][36] and applied as a cosmological frame work of the universe [37][38][39][40][41][42][43][44][45][46]. Recently, different dark energy models have been studied in the framework of Horava-Lifshitz cosmology using different infrared cut-offs.…”
Section: Introductionmentioning
confidence: 99%